Advances in antibody phage display technology. Issue 8 (August 2022) - Ledsgaard, Line; Ljungars, Anne; Rimbault, Charlotte; Sørensen, Christoffer V.; Tulika, Tulika; Wade, Jack; Wouters, Yessica; McCafferty, John; Laustsen, Andreas H.
Highlights: Antigen presentation strategy is important for the antibody selection campaign. Phage display selection strategy can be tailored to individual selection campaigns. Specialized libraries can be constructed to benefit specific discovery projects. The selection strategy determines the characteristics of the discovered antibodies. Abstract: Phage display technology can be used for the discovery of antibodies for research, diagnostic, and therapeutic purposes. In this review, we present and discuss key parameters that can be optimized when performing phage display selection campaigns, including the use of different antibody formats and advanced strategies for antigen presentation, such as immobilization, liposomes, nanodiscs, virus-like particles, and whole cells. Furthermore, we provide insights into selection strategies that can be used for the discovery of antibodies with complex binding requirements, such as targeting a specific epitope, cross-reactivity, or pH-dependent binding. Lastly, we provide a description of specialized phage display libraries for the discovery of bispecific antibodies and pH-sensitive antibodies. Together, these methods can be used to improve antibody discovery campaigns against all types of antigens.